A three-stage method for analyzing market concentration and airport efficiency in the Yangtze river Delta - Xinsheng Yang; Yang Zhang; Ming Wei (Scientific Reports)
Abstract With ongoing development of ground transportation system, competing regional airports need to collaborate in order to improve their efficiency and passenger turnover. However, finding the most advantageous dynamic connection between airports’ rivalry and collaboration, passenger market alterations, and influencing factors is quite challenging. To this end, our study proposed a three-stage method combining analytical methodologies and data envelopment analysis (DEA) to analyze the changing trend and correlation of passenger market concentration as well as operational efficiency in ten airports of China’s Yangtze River Delta (YRD) airport group during period from 2011 to 2019, China. As the first step, the current study applied state-of-the-art evaluative methods, including the Hirschmann-Hefenthal index, Gini index, and net-shift effects analysis, to examine passenger concentration. Subsequently, the super-efficiency data envelopment analysis (DEA) model was utilized to explore the correlation of net shift with airport performance. Finally, the OLS model was combined to make a comprehensive analysis. The proposed approach was discussed in detail and yielded the following findings. The YRD airport group was moderately concentrated and had a decentralized trend from 2010 to 2019. Half of the airports in the airport group had an efficiency score lower than one but managed to gain significant market shares in the competition. The analysis shows that in the Yangtze River Delta Airport Group, there is a significant positive correlation between market share and airport efficiency, while Net shift is only negatively correlated with airports that gain market share. The super-efficiency score curve of three airports changed dramatically, presenting a “U” shape, while that of the other seven airports changed steadily, related to their urban economic scale, urban development stage, and government investment pattern.